1994
DOI: 10.1183/09031936.94.07122169
|View full text |Cite
|
Sign up to set email alerts
|

Low plasma concentrations of VIP and elevated levels of other neuropeptides during exacerbations of asthma

Abstract: Neuropeptides in the lung occur in neurons, neuroendocrine and inflammatory cells. Their widespread distribution and physiological effects suggest that they may play important roles in asthma. We investigated whether, during an exacerbation of asthma, patients displayed changes in plasma levels of the neuropeptides vasoactive intestinal peptide (VIP), calcitonin gene-related peptide (CGRP), substance P (SP), and neuropeptide Y (NPY). Venous blood from 25 adult patients attending the emergency ward with an exac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
45
0
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(51 citation statements)
references
References 28 publications
5
45
0
1
Order By: Relevance
“…Moreover, Npy polymorphisms are associated with increased risk for asthma in overweight subjects (18,25). Other reports have demonstrated that plasma levels of NPY were increased in asthmatics at rest and in acute exacerbations (26)(27)(28). Our study shows that increased expression of Npy in airway epithelium can induce an AHR phenotype in a paracrine manner (Supplemental Figure 6).…”
Section: Resultssupporting
confidence: 49%
“…Moreover, Npy polymorphisms are associated with increased risk for asthma in overweight subjects (18,25). Other reports have demonstrated that plasma levels of NPY were increased in asthmatics at rest and in acute exacerbations (26)(27)(28). Our study shows that increased expression of Npy in airway epithelium can induce an AHR phenotype in a paracrine manner (Supplemental Figure 6).…”
Section: Resultssupporting
confidence: 49%
“…Since higher peripheral blood NPY, SP and CGRP concentrations and lower VIP levels have been found in bronchial asthma patients compared to normal subjects [30], it is possible that they can exacerbate the symptoms through favoring the Th2 balance. This is also consistent with the findings concerning multiple sclerosis (MS) which is thought to be associated with an excessive Th1 response.…”
Section: Discussionmentioning
confidence: 99%
“…Upregulation of VIP was detected in neurogenic inflammation in the rat retina (Bronzetti et al, 2007). Plasma VIP level of patients with acute asthmatic exacerbations was found to be significantly lower compared to the controls and showed correlation with the response to therapy, suggesting that bronchodilatory and vasodilatory actions of the peptide are essential in this regard (Cardell et al, 1994;Said, 1982). Even in a human study, VPAC2 receptor was shown to exert inhibitory action against bronchial asthma (Lind en et al, 2003).…”
Section: Discussionmentioning
confidence: 99%